Meningkatkan Pengetahuan dan Keterampilan Perawat dalam Merawat Bayi di NICU Melalui Latihan Asuhan Perkembangan - Ayuda Nia Agustina; Yeni Rustina; Ice Yulia (STIKes Persada Husada Indonesia, 2018)
Care development appliation by nurses is essential to minimize pain and stress, however not al nurses have yet to understand about care development. This study identifies the influence of providing developmental education through videos and pocket books. Study layout applied pre-test post-test equivalent group quasi experiment involving 34 NICU nurses divided into 2 groups (control and intervention) chosen from total sampling method. D ata analysis applied SPSS software with dependant test t-test. Study result showed there was a significant knowledge and skill difference between te control and intervention groups (p=0,000), and not found the relation between nurses’ characteristics (age, education, lenth of employment,training history) with knowlede and skill (p>0,05). Education on care development is essential for nurses and for care development application to be optimized.